A boranil-based conjugated microporous polymer for efficient visible-light-driven heterogeneous photocatalysis. Issue 21 (12th May 2021) - Gong, Weitao; Deng, Xiaorong; Dong, Kaixun; Liu, Lu; Ning, Guiling
Abstract : A new boranil-dye-incorporated conjugated microporous polymer was designed and employed as an effective heterogeneous photocatalyst for aerobic oxidation of sulfides and primary amines. Abstract : The incorporation of pure organic dyes into the backbone of conjugated microporous polymers (CMPs) opens a new avenue for facile construction of metal-free heterogeneous photocatalysts with tailor-made properties. Herein, we presented the design and synthesis of a new CMP based on a boranil dye which was exploited as an efficient heterogeneous photocatalyst. It exhibited superior photocatalytic performance towards aerobic oxidation of amines and sulfides compared with that of the boranil-free counterpart and featured wide visible-light absorption, a narrow optical bandgap, and more planar π-conjugation due to boron complexation. The present study establishes boranil dyes as efficient building blocks for fabricating new photocatalysts.